PENGUKURAN KINERJA DOSEN UNSERA DENGAN PENDEKATAN BALANCED SCORECARD - Suryaman Suryaman; Hamdan Hamdan (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This study reports performance of lecturers of Serang Raya University (UNSERA) measured using scorecard balanced approach.  This study used survey method describing findings in numerical data and narrative data each of which was incurred in four perspective measures: finance, students’ satisfaction, business, and growth and instruction. Data were collected using questionnaire, documents, and Focus Group Discussion.  The study revealed that description of research and social charity in 2011-2014, (1) finance perspectives showed that lecturer incurred small attainment as lecturers received small amount of donor provided by other institutions;   (2) a significant increase was achieved in perspectives of growth and instruction in that lecturers were motivated to conduct researches and improved teaching-learning performances; (3) in all, lecturer performance of UNSERA was good, indicated by the increase of journal articles published in national and international journals.